CHARACTERISTICS OF WASTEWATER IMMERSION MEMBRANE BIOREACTOR (Municipal economy of cities. Series: «Economy science», 2013)
The experience of operating a membrane bioreactor (MBR) for wastewater treatment, analysis of the main indicators of the effectiveness of ICBMs.